Stability of mechanically alloyed Al70Cu15Ni 15 alloy during annealing - Yadav, T.P.; Mukhopadhyay, N.K.; Tiwari, R.S.; Srivastava, O.N. (Institute of Physics Publishing, 2010)
A nano τ3 vacancy-ordered phase in the Al-Cu-Ni alloy system has been synthesized with a composition close to Al70Cu 15Ni15 by mechanical alloying a mixture of elemental powder in a high-energy ball mill by varying milling time from 10 to 100 hours. The stability of nano-crystalline τ3 vacancy-ordered phase has been studied under thermal annealing in vacuum as well as in air. The x-ray diffraction and transmission electron microscopy techniques were employed for characterization of the milled and annealed samples. The powder after 100 h of milling was found to contain mostly nano τ3 phase with the partial ordering, and with crystallite sizes in the range of 10-20 nm along with a lattice strain of ∼0.67 %. The milled powder, after annealing in vacuum at 700 °C for 60 h, revealed the formation of a strain-free and ordered τ3 phase with a crystallite size of 80 nm, indicating grain coarsening. It is interesting to note that the milled powder annealed in air at 700 °C for 60 h showed the formation of (Cu,Ni)Al2O4 type spinel phase with the lattice parameter of 8.1 Å and the lattice strain as 0.52 %. The average grain size of spinel phase was found to be ∼ 40 nm.
Keywords: High resolution transmission electron microscopy; Transmission electron microscopy; Annealing in vacuum; Thermal-annealing